DISTRIBUTION OF RARE EARTH ELEMENTS IN METAMORPHIC ROCKS OF PLATTENKALK GROUP AT CENTRAL CRETE, GREECE - Stathogianni, F.; Manoutsoglou, E.; Staboliadis, I.; Pantelaki, O.; Kallithrakas-Kontos, N. (Bulletin of the Geological Society of Greece, 2016)
Within the metamorphic rocks of the Plattenkalk Group, in an occurrence at Tallaia Mountains, central Crete, light rare earth elements Cerium and Lanthanum are found. The studied rare earths are seen in an epidote group mineral, allanite. Scanning Electron Microscopy of the samples showed clearly the crystals of allanite (prekinematic crystals) and their grain size. Mineral processing was conducted for the size fractions: (<10 μm), (10-212 μm) and (212-1000 μm), according to the magnetic properties and grain size of allanite. After magnetic separation of the fraction (<10 μm) and (212-1000 μm) rare earths Ce and La were observed to have higher concentrations in the magnetic products. In conclusion, (according to the microscopic and mineral processing data) the optimum grain size for the beneficiation of allanite is the size fraction (10-212 μm).